2000
DOI: 10.1002/1096-9861(20000918)425:2<202::aid-cne4>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of NGF and NT-3 on embryonic trigeminal axon growth patterns

Abstract: We examined the effects of neurotrophins nerve growth factor (NGF) and neurotrophin-3 (NT-3) on trigeminal axon growth patterns. Embryonic (E13-15) wholemount explants of the rat trigeminal pathway including the whisker pads, trigeminal ganglia, and brainstem were cultured in serum-free medium (SFM) or SFM supplemented with NGF or NT-3 for 3 days. Trigeminal axon growth patterns were analyzed with the use of lipophilic tracer DiI. In wholemount cultures grown in SFM, trigeminal axon projections, growth pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 78 publications
3
43
0
Order By: Relevance
“…Exogenous application of NGF and NT-3 to these cultures has differential effects on growth parameters of central trigeminal axons in the brainstem. In the presence of NGF, TG axons leave the central trigeminal tract and extend into the surrounding brainstem tissue without branching, whereas NT-3 promotes precocious arborization of tract axons (Ulupinar et al, 2000a). Localized application of neurotrophins also yields similar results .…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Exogenous application of NGF and NT-3 to these cultures has differential effects on growth parameters of central trigeminal axons in the brainstem. In the presence of NGF, TG axons leave the central trigeminal tract and extend into the surrounding brainstem tissue without branching, whereas NT-3 promotes precocious arborization of tract axons (Ulupinar et al, 2000a). Localized application of neurotrophins also yields similar results .…”
Section: Introductionmentioning
confidence: 79%
“…However, when NGF is added to the SFM, many axons grow outside the tract and elongate medially or laterally within the brainstem (n = 8; Fig. 2C; see also Ulupinar et al, 2000a). Quantitative and statistical analyses also indicated that there is more growth medially than laterally within the brainstem explants (Fig.…”
Section: Effects Of Ngf On Central Trigeminal Axon Growth Patternsmentioning
confidence: 85%
See 3 more Smart Citations